Internet connectivity disruption in Ethiopia (Ethiopia) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity disruption detected in Ethiopia. Data sourced from IODA.
Network Disruption Incident ID: ET-2026-0053. Severity: critical. Confidence: 65%